Pathological changes in the organs of mice model inoculated with Corynebacterium pseudotuberculosis organism - Abdullah, Faez Firdaus Jesse; Lau, Sang Sang; Saharee, Abdul Aziz; Shamsudin, Shahirudin (Universiti Putra Malaysia Press, 2011)
Corynebacterium pseudotuberculosis is a facultative, gram positive intracellular small club-shaped rod which produces lesions similar to those of tuberculosis. It is known worldwide to cause caseous lymphadenitis (CLA) in sheep and goats. CLA is characterized by the abscess formation in lymph nodes and/or visceral organs. In the recent outbreak of CLA in the TPU farm in UPM, it was reported that the CLA lesions were found in the visceral organs. In the present investigation, attempts were made to study the ethiopathogenesis of CLA in mice models which involved a comparison of clinical signs, haemogram and biochemistry, and histopathological changes in visceral organs between the diseased and non-diseased group. As an overall summary of this project, CLA in mice resulted in clinical signs, such as huddling together, dejection, anorexia, pasty faeces and accompanied by a rapid and shallow respiration pattern. For the haemogram and serum biochemistry profile, it showed a significant difference in the mean value between the diseased group and non-diseased group which include lymphocyte, plasma protein, monocyte, eosinophil, total bilirubin, total protein and potassium. Finally, the most pronounced histopathological changes in the visceral organs were septicaemia, with severe congestion and increased vascularization, together with the presence of capsulated abscess, micro-abscesses formation, infiltration of neutrophils and macrophages, tubercule granulomas, necrosis and early signs of degeneration in majority of the infected mice.